OSP-Immunofluorescent remyelinating oligodendrocytes in the brainstem of toxically-demyelinated Wistar rats Oligodendrócitos remielinizantes positivos para OSP - proteína específica do oligodendrócito- no tronco encefálico de ratos Wistar desmielinizados toxicamente - Eliza Simone Viégas Sallis; Cinthia Melazzo Mazzanti; Alexandre Mazzanti; Luis Antonio Violin Pereira; Kélen Fabíola Arroteia; Rafael Fustigatto; Charles Pelizzari; Aline Rodrigues; Dominguita Lühers Graça (Arquivos de Neuro-Psiquiatria)
Central nervous system (CNS) remyelination following toxically-induced demyelination is a well known process. Oligodendrocytes constitute the bulk of the myelinating cells in the brain whereas Schwann cells overwhelm oligodendrocytes numbers in spinal cord remyelination. Despite the common knowledge of these facts, we still do not know completely the origin of both remyelinating cells. The present study investigated the participation of mature oligodendrocytes in remyelination after ethidium-bromide (EB) induced demyelination in the brainstem of normal and cyclosporin A-immunosuppressed Wistar rats. Thirty adult female rats were divided into three experimental groups. In group 1 the rats received a single intracisternal injection of 10 muL of 0.1% ethidium bromide (EB) in 0.9% saline (n=10); in group 2 the rats received the EB injection while immunosuppressed with cyclosporin A (n=10); in group 3 the rats received a single 10 muL injection of 0.9% saline while treated with cyclosporin A. The rats were killed at 15, 21 and 31 days after injection. Within the EB lesions, from 15 days onward many cells within the periphery of the lesions stained positive for OSP (oligodendrocyte specific protein) a marker for mature oligodendrocytes and myelin. This cell marking signals that, at least, part of the process of repairing the myelin sheaths is carried out by mature cells of the oligodendrocyte lineage. A remielinização do sistema nervoso central após desmielinização tóxica é um processo bem conhecido. No encéfalo, os oligodendrócitos remielinizam uma área maior do que na medula espinhal, onde as células de Schwann são preponderantes. Embora esses fatos sejam bem conhecidos, ainda não se conhece com certeza a origem das células remielinizantes. Esta investigação foi desenhada para esclarecer a participação de oligodendrócitos maduros na reconstrução das bainhas perdidas após a desmielinização induzida por brometo de etídio (BE) no tronco encefálico de ratos Wistar normais e imunossuprimidos com ciclosporina A. Trinta ratos fêmeas adultas foram divididos em três grupos experimentais. No grupo 1, os ratos receberam uma injeção de 10 miL de BE em 0,9% salina (n=10) na cisterna basal; no grupo 2, os ratos receberam a injeção de BE e foram tratados com ciclosporina A (n=10); no grupo 3 os ratos receberam uma injeção de 10 miL de 0,9% salina e foram tratados com ciclosporina A. Os ratos foram sacrificados aos 15, 21 e 31 dias após a injeção. A partir dos 15 dias muitas células da periferia das lesões tiveram marcação positiva para OSP (proteína específica do oligodendrócito), marcador de oligodendrócitos maduros e mielina. Assim, foi possível comprovar que células maduras da linhagem oligodendroglial participam do processo de remielinização neste modelo gliotóxico.